Improvement Strategy to Reduce Delay in Returning Inpatient Medical Record at Jenggawah Primary Health Center in 2023 - Nuraini, Novita; Febriyanti, Bella Amalia; Wijayanti, Rossalina Adi (Indonesian Journal Publisher, 2024)
Delay return of inpatient medical records still occur at Jenggawah Primary Health Center with an average percentage 52,15%. This situation leads to misfiled records, potentially causing disruptions and errors in patient care. The purpose’s research was to develop a strategy to reduce delay return of inpatient medical records using action research. This research methodology is quasi-semi-experimental methodology, incorporating interviews, observations, documentation, and discussions for data collection. Results in diagnosing action, the delay in returning the medical record of inpatient was caused by the officers' lack of medical record knowledge and their lack of medical record training, the contents of the SOP, which required evaluation, and the tracer's inadequate work. Planning action to plan strategy which are hold medical record training, reviewing returning medical record’s SOP and redesigning tracer. Taking action to implement strategy during 3 month. There is the evaluation action, which includes 4 success parameters. Overall, it is considered successful if the percentage of delays in returning inpatient medical records is dropped to a maximum of 50% per month. Evaluating action to evaluate taking action were carried out properly because the percentage of delays in returning inpatient medical record was reduced below 50%. It’s hoped medical recorder always monev and remind each other regarding the return of inpatient medical records. And it’s hoped Jenggawah Primary Health Center will hold in house training, hold socialization of SOP and budgeting funds for supporting facilities.